2017
DOI: 10.5327/z1677-606220172077
|View full text |Cite
|
Sign up to set email alerts
|

Composição, riqueza e categorias de ameaça das espécies arbóreas da Amazônia

Abstract: Resumo:A Amazônia é a região com a mais alta biodiversidade do mundo, mas ainda há muitas lacunas sobre o conhecimento de suas espécies e relações ecológicas. Entretanto, a Amazônia também corresponde à região mundial com a maior média de desmatamento, despontando significativamente na derrubada de espécies arbóreas. Nosso objetivo foi investigar a composição da vegetação arbórea da Amazônia conforme categorias de ameaça de extinção e endemismo. Utilizamos a lista de árvores do domínio da Amazônia do banco de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
2
1
1
Order By: Relevance
“…The number of endemic species of Brazil and of the Atlantic Forest in the present study was lower than the number recorded in a study carried out in the municipality of Faria Lemos, MG (Rocha et al, 2017) and higher than that found in the Brazilian Amazon (Oliveira et al, 2017). When evaluating the EG -Ecological Group: P -Pioneer; IS -Initial Secondary; LS -Late Secondary.…”
Section: Discussioncontrasting
confidence: 85%
“…The number of endemic species of Brazil and of the Atlantic Forest in the present study was lower than the number recorded in a study carried out in the municipality of Faria Lemos, MG (Rocha et al, 2017) and higher than that found in the Brazilian Amazon (Oliveira et al, 2017). When evaluating the EG -Ecological Group: P -Pioneer; IS -Initial Secondary; LS -Late Secondary.…”
Section: Discussioncontrasting
confidence: 85%
“…Among the greatest phytogeographic domains in the world, the Amazon is considered the largest tropical forest (Oliveira et al 2017), sheltering a signifi cant portion of biodiversity with different levels of richness (Vieira et al 2018). The variability of fauna and fl ora species of different taxonomic groups in this region has been lost with deforestation, a consequence of anthropic spatial occupation that is one of the most predatory forms of land use (Yanai et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One of the strategies to reduce the pressure of forest exploitation and reduce the risk of extinction of several species is through planting in agroforestry systems, or in monoculture (OLIVEIRA et al, 2017), which allows, in addition to the production of wood with economic potential (VIEIRA et al, 2011), increase the sustainability of the sector, reducing the negative impacts that exploration causes.…”
Section: Introductionmentioning
confidence: 99%